Potential of Flavonoid Isolate from Okra Fruit (Abelmoschus esculentus L.) as Antidiabetic and Antilipase Agent In Vitro and In Silico - Astutiningsih, Christina; Meri , Meri (Jurnal Farmasi Sains dan Terapan (Journal of Pharmacy Science and Practice), 2025)
Obesity, which is currently a global issue that contributes to a number of diseases, including diabetes and coronary heart disease. This study set out to isolate and identify the flavonoid compounds from okra fruit that demonstrate the ability to inhibit alpha glucosidase and pancreatic lipase. Okra fruit powder was extracted using ethanol at a concentration of 80% following fractination with n-hexane, ethyl acetate, and aquadest. TLC preparation was used to isolate flavonoid from fraction ethyl acetate. Flavonoids that were succesfully isolated were quercetin compounds. The IC50 value of quercetin was found to be 47.9763 micrograms/mL. This was greater than IC50 acarbose as a positive control at a concentration of 33.8169 micrograms/mL, which showed its ability as an inhibitor -glucosidase was smaller. Quercetin acted as pancreatic lipase inhibitors, albeit weaker than the positive control Orlistat, which at the same concentration could inhibit 68% of pancreatic lipase activity, while quercetin could only inhibit 50%. Using molecular docking in silico testing, quercetin compounds were shown to have a stronger bond than the positive control. Similar to positive control, quercetin compounds could interact with receptors with amino acids residues GLU 277 (glutamic acid) and ASP 352 (aspartic acid), amino acids crucial in determining enzyme activity. Conversely, in the silico tests for  pancreatic lipase inhibition, Orlistat  displayed an exceedingly strong bond than quercetin compounds. Despite this, quercetin compounds also showed interaction between resceptors with amino acids residues MET 123 (Methionine) and ALA 51 (Alanine), amino acids that determine enzyme activity (catalytic site of enzyme)